Fixation of Displaced Avulsion Fracture of the Anterior Superior Iliac Spine (ASIS) after Bone Graft Harvesting Using Anatomic Low-Profile Locking Plate: Case Report and Surgical Technique - Aurich, Matthias; Hofmann, Gunther O. (Zeitschrift für Orthopädie und Unfallchirurgie, 2020)
Bone graft harvesting from the anterior iliac crest is a frequently performed surgical procedure widely used to treat bone defects in orthopedic trauma and reconstructive surgery. Fracture of the iliac crest or avulsion of the anterior superior iliac spine (ASIS) is a potential complication. Displaced fractures require surgical treatment, i.e., reconstruction of the bone defect and fixation of the ASIS fragment. Here, the surgical technique using a special anatomic low-profile locking plate and the strategy of defect reconstruction using allograft cancellous bone are described and their advantages are discussed. We are convinced that it is a safe procedure that can be used for fracture fixation and donor site stabilization during the index procedure.
Keywords: iliac crest; bone harvest; fracture fixation; defect reconstruction